Electrically conductive NBR/CB flexible composite film for ultrastretchable strain sensors: fabrication and modeling - Qu, Muchao; Qin, Yijing; Xu, Wei; Zheng, Zhenxing; Xu, Huagen; Schubert, Dirk W.; Gao, Qun (Applied Nanosciene, 2021)
In this study, a flexible strain sensor with ultrahigh stretchability, outstanding sensitivity, and excellent repeatability based on conductive carbon black (CB) and nitrile butadiene rubber (NBR) was presented. Two organic solvents with three different coating time during the dissolve-coating process were investigated. The morphology and the degradation temperature of all the NBR/CB composite films were studied, and the tensile strength, elongation at break, as well as the young’s modulus and the dissipated energy for all the specimen were revealed. The strain-sensing tests indicated that the NBR/CB film possess a good sensitivity (max. gauge factor = 24.9) and an ultrahigh sensing range (max. 681% strain). The mathematic model from Simmons for predicting the sensing behavior based on the tunneling theory was further simplified, and a novel equation was proposed for predicting the relative change of resistance as a function of time during the cyclic test, which showed great agreement with the cyclic strain-sensing data in experiments. Overall, this study introduces a simple low-cost fabrication method for preparing the polymeric flexible strain sensors with great strain-sensing performance. The development of the two mathematical modellings makes several noteworthy contributions to the existing knowledge of strain-sensing behavior.
CRIS-Team Scopus Importer:2021-01-08
Keywords: Carbon black; Modeling; Nitrile butadiene rubber; Strain sensor; Ultrastrechable